2018
DOI: 10.1111/ijfs.13887
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the process, temperature, light and oxygen on naringin extraction and the evolution of its antioxidant activity

Abstract: Summary Citrus co‐products are rich in flavonones among them naringin. This compound exhibits several biological activities. These properties are mainly due to its antioxidant activity. The purpose of this work was in one hand to compare five technics of extraction conducted under different operating conditions and in the other hand, to analyse the effects of temperature, light and oxygen on naringin degradation and on the evolution of its antioxidant activity. The results obtained showed that the ultrasound a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…This could be explained with the biological activity which phenols and flavonoids compounds possess beside their chemical activity. The effects of different extraction techniques on antioxidative compounds were investigated by Ioannou, M'hiri, Chaaban, Boudhrioua, and Ghoul () where the extraction of naringin from peels from fresh orange was performed and results showed that the UAE provided the highest naringin content.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be explained with the biological activity which phenols and flavonoids compounds possess beside their chemical activity. The effects of different extraction techniques on antioxidative compounds were investigated by Ioannou, M'hiri, Chaaban, Boudhrioua, and Ghoul () where the extraction of naringin from peels from fresh orange was performed and results showed that the UAE provided the highest naringin content.…”
Section: Resultsmentioning
confidence: 99%
“…Obtained antioxidant activity in dried cornelian cherries extracts observed with three different tests DPPH, FRAP, and ABTS was in the range from 0.0248 to 0.1218 mM TE/g, from 0.0303 to 0.0756 mM Fe 2+ /g, and from 0.4389 to 0.9507 mM TE/g, respectively (Table 2). were investigated by Ioannou, M'hiri, Chaaban, Boudhrioua, and Ghoul (2018) where the extraction of naringin from peels from fresh orange was performed and results showed that the UAE provided the highest naringin content.…”
Section: Effects Of Extraction Parameters On Biological Compounds mentioning
confidence: 99%
“…Flavonoids are very sensitive to environmental conditions and are therefore very subject to degradation phenomena [ 115 ]. Luteolin, quercetin, and kaempferol were successfully encapsulated in liposomes; in this research work, the liposomal system was shown to be useful in protecting flavonoids and in keeping their antioxidant properties [ 116 ].…”
Section: Nanotechnology As a Nutraceutical Properties Enhancement mentioning
confidence: 99%
“…Some studies have found that hesperidin possesses anti-inflammatory, lipid-lowering, antioxidant and anticancer biological and pharmacological properties (Bok et al, 1999;Choi et al, 2001). Moreover, it can also form metal complexes through the coordination of carbonyl and hydroxyl groups with metal ions to enhance water solubility and bioavailability (Ioannou et al, 2018). Under the action of rhamnosidase, the main hydrolyzed products were monoglycoside flavonoids named HMG which possesses a variety of pharmacological and biochemical activities, as well as anti-inflammatory, antiviral, and anticancer effects (Grazul and Budzisz, 2009).…”
Section: Introductionmentioning
confidence: 99%